(untitled) (Revista de Psicología, 2022)
This article presents a theoretical analysis of imagination from developmental psychology, pointing out its links with creativity. Imagination is a collective enterprise and is defined as an integrating and flexible function, which consists in the generation, from previous knowledge, of new ideas and possibilities. Imagination helps not only construct unreal or fantastic worlds, but also construct realities and transform the world, like occur in creatives’ process. Finally, a reflection about the importance of fostering rich contexts that contribute to the development of imagination in childhood is made.